2010
DOI: 10.1088/0004-637x/723/1/544
|View full text |Cite
|
Sign up to set email alerts
|

SPECTRO-INTERFEROMETRY OF THE Be STAR δ Sco: NEAR-INFRARED CONTINUUM AND GAS EMISSION REGION SIZES IN 2007

Abstract: We present near-infrared H and K-band spectro-interferometric observations of the gaseous disk around the primary Be star in the δ Sco binary system, obtained in 2007 (between periastron passages in 2000 and 2011). Observations using the CHARA/MIRC instrument at H-band resolve an elongated disk with a Gaussian FWHM 1.18 × 0.91 mas. Using the Keck Interferometer, the source of the K-band continuum emission is only marginally spatially resolved, and consequently we estimate a relatively uncertain K-band continuu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
(33 reference statements)
7
13
1
Order By: Relevance
“…a Brγ = 3.6 ± 0.6 R and a HeI = 4.2 ± 0.8 R . Moreover, the size of the Hα emission obtained from our CHARA/VEGA measurements is also roughly compatible with the Millan-Gabet et al (2010) estimation using the line EW, i.e., 14.9 R . Consequently, it seems that the disk did not grow or shrink during the 2007-2010 period.…”
Section: The Circumstellar Disk Extensionsupporting
confidence: 86%
See 2 more Smart Citations
“…a Brγ = 3.6 ± 0.6 R and a HeI = 4.2 ± 0.8 R . Moreover, the size of the Hα emission obtained from our CHARA/VEGA measurements is also roughly compatible with the Millan-Gabet et al (2010) estimation using the line EW, i.e., 14.9 R . Consequently, it seems that the disk did not grow or shrink during the 2007-2010 period.…”
Section: The Circumstellar Disk Extensionsupporting
confidence: 86%
“…Modeled as a Gaussian distribution, the respective FWHM are a Hα = 9.0 ± 3.0 R , a Brγ = 5.5 ± 1 R , and a HeI = 4.5±0.5 R . The disk extensions in the infrared lines are compatible with those derived by Millan-Gabet et al (2010) from 2007 Keck-Interferometer measurements, i.e. a Brγ = 3.6 ± 0.6 R and a HeI = 4.2 ± 0.8 R .…”
Section: The Circumstellar Disk Extensionsupporting
confidence: 86%
See 1 more Smart Citation
“…δ Sco is also a binary Be star already observed by Millan-Gabet et al (2010) in 2007 with CHARA and resolved in the H continuum, Brγ, HeI and Hα lines. This is an interesting system since the companion passage at periastron is so close that tidal effects have strong effects on the formation/dissipation of the circumstellar disk around the primary.…”
Section: δ Scomentioning
confidence: 76%
“…The Be star delta Sco was studied by combining KI and CHARA observations 21 . These authors found the K-band continuum emission was only marginally spatially resolved, while line emission from He I λ2.0583 μm and Br γ λ2.1657 μm was clearly detected with ~10% lower visibilities than those of the continuum.…”
Section: B2 Starsmentioning
confidence: 99%